MICROSCOPIC IDENTIFICATION OF VESICULAR ARBUSCULAR MYCORRHIZAE (VAM) ASSOCIATED WITH ORCHID Cymbidium sp. - Gresia Eldina; I Gede Putu Wirawan; Made Sritamin (Central Laboratory for Genetic Resource and Molecular Biology, Faculty of Agriculture, Udayana University in cooperation with Asia-Oceania Bioscience and Biotechnology Consortium (AOBBC), 2021)
Cymbidium sp. is one of the most popular orchid desired in public, it means high productivity is needed in its fulfillment. One of the obstacle of Cymbidium sp. orchid in order to fullfilment of productivities are the stress and orchid’s seed size which is very small. Vesicular Arbuscular Mycorrhizae is a symbiont fungus that can help absorption of nutrients in stress phase. VAM help Cymbidium sp. to maintenance and increase the productivity. This research aimed to determined VAM species and colonization in rhizospher of Cymbidium sp. orchid. This research has been conducted from November 2020 untill April 2021. Spore isolation was conducted by using wet shievings method, meanwhile VAM colonization was conducted by using roots staining techniques. The result showed there were 4 genus consisted by 6 different type of spores which has been found. There was Glomus (2 types), Dentiscutata (2 types), Acaulospora (1 type), and Gigaspora (1 type). Colonization of VAM in sample plant has been known by presence of VAM special structure, there were vesicular and internal hyphae.